TEKNIK SELF MANAGEMENT DALAM KONSELING KELOMPOK UNTUK MEREDUKSI PROKRASTINASI PELAJAR DI DESA SOROSUTAN - AZIZ INMAS PRASETYA; MATURIDI - MATURIDI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2021)
This study aims to determine self-management techniques in group counseling to reduce student procrastination. This study uses a pre-experimental design one group pre-test-pot-stest design method . In practice, the experimental group was given treatment in four group counselling sessions using self-management techniques. Determination of the subject of this study using purposive sampling technique, the subjects in this study were students in the village of Sorosutan Umbulharjo Yogyakarta. The students who became the sample were 6 people with a high level of academic procrastination. The instrument used in this study used a Likert scale consisting of 39 valid items with reliability showing that the r alpha for the academic procrastination variable was 0.869. The analysis technique used descriptive statistical data analysis. The results of the research hypothesis show that the value of Sig (0.000) < (0.05) , which means that there is a difference in students' academic procrastination scores between before and after being given self-management techniques in group counseling , which means that self-management techniques in group counseling are effective for reduce student academic procrastination in Sorosutan Umbulharjo village, Yogyakarta.